(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
The adaptation of employees in an organization is an important part of the human resource management system. At the beginning of his career, an employee inevitably faces a large number of difficulties, the bulk of which arise due to the lack of information about the order of work, criteria for evaluating work, peculiarities of relationships between colleagues, etc. In addition, when applying for a job, an employee finds himself faced with the need to accept the organizational requirements imposed by the organization, to reconsider his views and habits, correlating them with the norms and rules of conduct accepted in the organization, traditions and values. The article presents an analysis of empirical data aimed at determining the socio-psychological determinants of women’s adaptation to public service